Enhancing Social Intelligence among Schizophrenia Patients at Maamoura Psychiatric Hospital: Evaluating the Effectiveness of a Recreational Program - Elalem, Saad Fathallah; Abdelwahab, Eman Abdelaziz; Ali, Mohamed Amjad; AbdElhafez, Shaymaa Abdelnaby (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aimed to investigate the effectiveness of a recreational program in enhancing the social intelligence of schizophrenia patients at Al-Maamoura Psychiatric Hospital. Methodology: The study employed an experimental approach, with a sample of 30 schizophrenia patients at Al-Maamoura Psychiatric Hospital in Egypt. This sample was divided into two groups: 10 cases for the exploratory study and 20 cases for the main study. Within the main study group, 10 cases were assigned to the experimental group (participating in the recreational program), while the remaining 10 comprised the control group. The researchers designed a social intelligence scale to collect data before and after the implementation of the recreational program, which spanned two months and included 16 therapeutic recreational sessions. Results: The study revealed that engaging in recreational activities resulted in a higher level of social intelligence among schizophrenia patients. This was evidenced by improvements in various dimensions of social intelligence: social empathy (73.01%), social self-efficacy (66.81%), social problem solving (65.45%), social information processing (44.65%), social skills (31.30%), and social awareness (30.96%) among the schizophrenia patients. Conclusions: Based on the results, the study recommends the incorporation of recreational therapy programs into the treatment and rehabilitation protocols for schizophrenia patients in healthcare facilities. Hence, efforts should be made to equip government hospitals and rehabilitation centers with the necessary resources, tools, devices, and recreational facilities.